การประเมินประสิทธิภาพระบบประปาหมู่บ้านในพื้นที่จังหวัดอุบลราชธานี EFFICIENCY ASSESSMENT OF VILLAGE WATER SUPPLY IN UBON RATCHATHANI PROVINCE - อำนาจ ยุภาพร; สุทธิประภา นันทพร; มาลัย วัฒนาชัย (Srinakharinwirot University Journal of Sciences and Technology, 2015)
บทคัดย่อ วัตถุประสงค์ของการศึกษานี้เพื่อประเมินการควบคุมและดูแลระบบผลิตประปาหมู่บ้าน คุณภาพน้ำประปา และการบริหารงานกิจการประปาของคณะกรรมการบริหาร โดยทำการสุ่มตัวอย่างระบบผลิตประปาทั้งสิ้น 110 แห่ง และใช้แบบสอบถามความคิดเห็นของคณะกรรมการและผู้ดูแลระบบ เก็บตัวอย่างน้ำประปาเพื่อตรวจวัดคุณภาพ การตรวจวิเคราะห์คุณภาพน้ำได้กำหนดพารามิเตอร์คือ ความเป็นกรด-ด่าง สีความขุ่น ของแข็งละลาย ความกระด้าง เหล็ก คลอไรด์ ไนเตรต โคลิฟอร์มและฟีคัลโคลิฟอร์มแบคทีเรีย เปรียบเทียบกับเกณฑ์คุณภาพน้ำประปา ปี พ.ศ. 2543 ของกรมอนามัย พบว่า คุณภาพน้ำประปาหมู่บ้าน 48% ไม่ผ่านเกณฑ์คุณภาพน้ำประปา ประสิทธิภาพในการบริหารจัดการโดยคณะกรรมการบริหารกิจการประปาอยู่ในระดับพอใช้ ผู้ดูแลระบบประปาหมู่บ้านยังขาดความรู้ความเข้าใจในการดูแลระบบเพราะขาดการได้รับการอบรมการผลิตประปาที่ถูกต้อง ดังนั้นจำเป็นต้องได้รับการปรับปรุงและพัฒนาต่อไป Abstract The objective of this research is the investigation of the assessment for control and operation of the village water supply plant, water quality and waterworks administration of the executive committee. Random samples of water supply were 110 samples and questionnaire of the board and administrator. Water samples were analyzed in terms of water quality such as pH, color, turbidity, dissolved solids, hardness, iron, chloride, nitrate, chloriform bacteria and fecal chloriform bacteria. It was compared with the water quality standard of the department of health (2000). Result showed that the village water supply quality of 48% not followed the water standard. Performance management by the committee in the waterworks is medium level. Water administrator is also lack of knowledge and understanding for water supply procedure due to lack trained properly. Therefore, the assessment for control and operation of the village water supply plant needs to be improved and developed in future.